Magnetic cores, magnetic components and electronic devices
By using large particles with a specific average aspect ratio and small particles of soft magnetic particles, the problem of difficulty in improving the loss and density when using metal magnetic powder is solved, and the voltage withstandability improvement is achieved under high relative magnetic permeability.
Patent Information
- Application Number
- CN202110307011.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-01-13
- Filing Date
- 2021-03-23
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2041-03-23
AI Technical Summary
When using metal magnetic powder in the existing magnetic core, the core loss is prone to increase, and it becomes difficult to increase the density of the powdered magnetic core during molding.
Soft magnetic particles with large particles and small particles having a specific average aspect ratio are used, and the voltage withstand characteristics of the magnetic core are improved by setting the average aspect ratio A1 of the large particles to 1.00≤A1≤1.50, the average aspect ratio A2 of the small particles to 1.30≤A2≤2.50, and A1
While maintaining a relatively high magnetic permeability, the voltage withstand characteristics of the magnetic core are significantly improved, solving the problem of difficulty in improving core loss and density.
Smart Images

Figure CN113436853B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a magnetic core, a magnetic component and an electronic device. Background Art
[0002] Patent document 1 describes an inductor formed by integrally molding a powder core obtained by compacting metal magnetic powder and a coil portion. However, when metal magnetic powder is used, the core loss tends to increase. Here, by using amorphous alloy powder as the metal magnetic powder, the core loss is improved. However, it is known that in this case, it becomes difficult to increase the density of the powder core during molding.
[0003] Patent Documents 2 and 3 propose to use a mixture of crystalline alloy magnetic powder and amorphous alloy magnetic powder.
[0004] Patent Document 4 describes that by using an amorphous soft magnetic powder having a high average practical sphericity, an inductor or the like having lower loss than that of the prior art can be provided.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2003-309024
[0008] Patent Document 2: Japanese Patent Application Publication No. 2004-197218
[0009] Patent Document 3: Japanese Patent Application Publication No. 2004-363466
[0010] Patent Document 4: Japanese Patent No. 5110660 Summary of the invention
[0011] Technical problem to be solved by the invention
[0012] An object of the present invention is to obtain a magnetic core or the like having improved withstand voltage characteristics while maintaining high relative magnetic permeability.
[0013] Technical solutions for solving technical problems
[0014] In order to achieve the above-mentioned purpose, the present invention provides a magnetic core, which includes large particles observed as soft magnetic particles with a Heywood diameter of 5 μm to 25 μm and small particles observed as soft magnetic particles with a Heywood diameter of 0.5 μm to 3 μm in cross section, and the average aspect ratio of the above-mentioned large particles is set to A1, and the average aspect ratio of the above-mentioned small particles is set to A2, satisfying 1.00≤A1≤1.50, 1.30≤A2≤2.50, and A1<A2.
[0015] It was found that the magnetic core of the present invention can improve the withstand voltage characteristics while maintaining the relative magnetic permeability at a high state because it uses large particles and small particles with a specific average aspect ratio, and makes the average aspect ratio of the small particles larger than the average aspect ratio of the large particles.
[0016] In the cross section, the maximum value of the Heywood diameter of the soft magnetic particles that are neither the large particles nor the small particles may be 40 μm or less.
[0017] The average ellipticity of the large particles in the cross section may be 0.93 or more.
[0018] The aforementioned large particles may include nanocrystals.
[0019] The above-mentioned small particles may contain Fe as a main component.
[0020] The small particles may contain Fe and at least one selected from Si and Ni as main components.
[0021] A magnetic component of the present invention includes the above-mentioned magnetic core.
[0022] The electronic device of the present invention includes the magnetic core. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is an example of a curve obtained by X-ray crystal structure analysis.
[0024] Figure 2 It is through Figure 1 An example of a graph obtained by performing peak shape fitting on the curve. DETAILED DESCRIPTION
[0025] Hereinafter, embodiments of the present invention will be described.
[0026] The magnetic core of the present embodiment includes large particles observed as soft magnetic particles having a Heywood diameter of 5 μm to 25 μm both inclusive, and small particles observed as soft magnetic particles having a Heywood diameter of 0.5 μm to 3 μm both inclusive, in cross section.
[0027] The total area ratio of the large particles relative to the entire cross section may be 10% or more, or 30% or more. The total area ratio of the small particles may be 10% or more, or 15% or more. In addition, the total area ratio of the large particles is set as S1, and the total area ratio of the small particles is set as S2, which may be S1:S2=1:9 to 9:1.
[0028] The Heywood diameter is the projected area circle equivalent diameter. Let the area of the soft magnetic particles on the cross section be S, and the Heywood diameter of the soft magnetic particles of this embodiment is (4S / π) 1 / 2 .
[0029] In addition, for the magnetic core of this embodiment, the average aspect ratio of large particles is set to A1, and the average aspect ratio of small particles is set to A2, and the magnetic core satisfies 1.00≤A1≤1.50, 1.30≤A2≤2.50, and A1<A2.
[0030] In addition, the large particles and small particles of this embodiment may have a coating on the surface. The coating may be an insulating film. The type of the coating is not particularly limited, as long as it is a coating formed by coating commonly used in the technical field. For example, iron oxides, phosphates, silicates (water glass), soda-lime glass, borosilicate glass, lead glass, aluminosilicate glass, borate glass, sulfate glass, etc. may be cited. As phosphates, for example, magnesium phosphate, calcium phosphate, zinc phosphate, manganese phosphate, and cadmium phosphate may be cited. As silicates, for example, sodium silicate may be cited. In addition, the thickness of the coating is not particularly limited. If it is a coating formed on a large particle, it may be an average of more than 5nm and less than 100nm. If it is a coating formed on a small particle, it may be an average of more than 5nm and less than 100nm. In addition, since the thickness of the above-mentioned coating is significantly lower than the particle size of each particle, it will not substantially affect the Heywood diameter and aspect ratio of each particle.
[0031] In addition, the magnetic core of this embodiment may have a resin used as a binder. The type of the resin is not particularly limited. For example, silicone resin or epoxy resin can be exemplified. The content of the resin in the magnetic core is also not particularly limited. For example, it can be 1.5 parts by mass or more and 5.0 parts by mass or less relative to 100 parts by mass of the soft magnetic particles.
[0032] Next, a method for observing the cross section of the magnetic core will be described.
[0033] First, a cross section obtained by cutting the magnetic core is polished to prepare an observation surface, and then the observation surface is observed using a SEM to capture a SEM image.
[0034] The size of the SEM observation range is not particularly limited, as long as more than 100 arbitrary large particles can be observed, preferably more than 1000 arbitrary large particles can be observed. In addition, different observation ranges can be set, SEM images of each observation range can be taken, and the above number of particles can be observed by summing up a plurality of SEM images.
[0035] The magnification of the SEM image is not particularly limited as long as the various parameters of the present embodiment can be measured, and can be, for example, 200 to 5000 times.
[0036] The aspect ratio of each soft magnetic particle is calculated by dividing the length of the major axis by the length of the minor axis.
[0037] The magnetic core of this embodiment can improve the withstand voltage characteristics while maintaining the relative magnetic permeability by making the average aspect ratio A1 of the large particles, the average aspect ratio A2 of the small particles, and the relationship between A1 and A2 as described above.
[0038] The reasons why the relative magnetic permeability and withstand voltage characteristics of the magnetic core of the present embodiment are improved are described below.
[0039] Regarding the withstand voltage characteristics of the magnetic core, the case where the contact between the soft magnetic particles contained in the magnetic core is surface contact and the case where the contact is point contact is compared, and it is easy to improve in the case of surface contact. In the case where the contact between the soft magnetic particles is point contact and surface contact, the contact area between the soft magnetic particles is large in the case of surface contact. Here, the larger the contact area between the soft magnetic particles, the smaller the voltage per unit area applied to the part of the soft magnetic particles in contact with each other when the voltage is applied. That is, when the contact between the soft magnetic particles is surface contact, the part where the electric field is concentrated when the voltage is applied is reduced. Thus, when the contact between the soft magnetic particles is surface contact, the withstand voltage characteristics of the magnetic core increase. In addition, the greater the degree of deformation of the soft magnetic particles contained in the magnetic core from the spherical shape, the easier it is for the contact between the soft magnetic particles to become surface contact. That is, it can be considered that the larger the aspect ratio of the soft magnetic particles, the easier it is to improve the withstand voltage characteristics of the magnetic core.
[0040] However, at the same time, when the aspect ratio of the soft magnetic particles is too large, the electric field tends to concentrate in the long axis direction of the soft magnetic particles when a voltage is applied. Due to the concentration of the electric field, the withstand voltage characteristics of the magnetic core are reduced. Therefore, simply increasing the aspect ratio of all soft magnetic particles is difficult to improve the withstand voltage characteristics of the magnetic core, and on the contrary, it may even be reduced.
[0041] The inventor of the present invention has found that the larger the aspect ratio of the soft magnetic particles is, the lower the withstand voltage characteristics of the magnetic core are, which is easy to occur in soft magnetic particles with larger particle sizes. And it is found that the withstand voltage characteristics are improved by making the small particles deform more than the large particles and increasing the aspect ratio of the small particles. The details of the reason why the withstand voltage characteristics are improved by increasing the aspect ratio of the small particles are not clear. However, it can be considered that compared with the situation of increasing the aspect ratio of the large particles to increase the proportion of surface contact, in the case of increasing the aspect ratio of the small particles to increase the proportion of surface contact, the part where the electric field is concentrated in the large particles when the voltage is applied is reduced. Therefore, it can be considered that the reduction of the withstand voltage characteristics can be suppressed by reducing the part where the electric field is concentrated in the large particles.
[0042] In addition, generally, when the filling rate of soft magnetic particles is increased, a tendency of relative magnetic permeability rising is shown. However, when the filling rate of soft magnetic particles is increased, the intervals between soft magnetic particles are narrowed. Therefore, when the filling rate of soft magnetic particles is increased, the positions where the electric field is concentrated increase when voltage is applied. Thus, generally, by increasing the filling rate of soft magnetic particles, the withstand voltage characteristic deteriorates.
[0043] That is, in the prior art, the relative magnetic permeability is improved by increasing the filling rate, but since the voltage withstand characteristics are deteriorated by increasing the filling rate, it is difficult to improve the voltage withstand characteristics under the state of high relative magnetic permeability. The inventors of the present invention have successfully improved the voltage withstand characteristics under the state of high relative magnetic permeability by setting both the aspect ratio of large particles and the aspect ratio of small particles within a specific range and making the aspect ratio of small particles greater than the aspect ratio of large particles.
[0044] The method for calculating the filling rate of the magnetic core is not particularly limited. For example, the above-mentioned observation surface is observed using SEM. Then, the area ratio of the particles relative to the entire observation surface area is calculated. Then, in this embodiment, the area ratio is regarded as equal to the filling rate, and the area ratio is used as the filling rate.
[0045] On the cross section, the maximum value of the Heywood diameter of the soft magnetic particles that are not the large particles or the small particles may be 40 μm or less. In other words, on the cross section, the Heywood diameter of the soft magnetic particles with the largest Heywood diameter may be 40 μm or less.
[0046] Furthermore, the Heywood diameter of the soft magnetic particles having the largest Heywood diameter in the cross section may be 25 μm or less. In other words, no soft magnetic particles having a Heywood diameter larger than that of the large particles may be observed in the cross section.
[0047] When the maximum value of the Heywood diameter of the soft magnetic particles that are not the above-mentioned large particles and the above-mentioned small particles exceeds 40μm, it is difficult to improve the withstand voltage characteristics of the magnetic core. This is because when the magnetic core contains soft magnetic particles with large Heywood diameters, the number of particles per unit length in the direction of applied voltage is reduced. In particular, when the particles are filled with resin, whether or not soft magnetic particles with large Heywood diameters are included tends to increase the difference in withstand voltage characteristics.
[0048] The average ellipticity of the large particles in the cross section may be 0.930 or more, and more preferably 0.950 or more.
[0049] In order to evaluate the shape of particles, 2×(π×cross-sectional area) is often used. 1 / 2 / (circumference of the cross section), but in the present embodiment, the shape of the particles is evaluated by ellipticity. The ellipticity is 4×cross-sectional area / (major axis×minor axis×π).
[0050] Generally, when the particles are flat, the circularity is low. However, even when the particles are flat, the elliptical circularity is also high. On the other hand, even when the particles are in a depressed shape or a skewed shape, the circularity is sometimes not low. However, when the particles are in a depressed shape or a skewed shape, the elliptical circularity is low. In addition, when the particles are in a shape with larger concavoconvex, the circularity and the elliptical circularity are both low. That is, in order to evaluate whether the particles are deformed beyond flatness from the perspective of a perfect circle, for example, whether the particles have depressions, skewnesses or concavoconvexities, it is sometimes preferred to utilize elliptical circularity.
[0051] Here, whether the large particles contained in the magnetic core are flat or not hardly affects the withstand voltage characteristics. However, whether the large particles are deformed other than flat, for example, whether the large particles contained in the magnetic core are concave, skewed, or have large bumps, easily affects the withstand voltage characteristics. This is because the fewer the points where the electric field is concentrated when the voltage is applied, the higher the withstand voltage characteristics of the magnetic core. As a result, the number of points where the electric field is concentrated is unlikely to depend on whether the large particles are flat, but is likely to depend on whether the large particles are deformed other than flat.
[0052] There is no particular restriction on the microstructure inside the soft magnetic particles. For example, the soft magnetic particles may have a structure containing amorphous matter or a structure composed of crystals. It is preferred that the large particles have a nano-heterogeneous structure containing initial microcrystals with an average crystal particle size of 0.3 nm or more and 10 nm or less in the amorphous matter. In addition, in the case where the soft magnetic particles have a structure or a nano-heterogeneous structure composed only of amorphous matter, the amorphous rate X described later is 85% or more. In the case where the soft magnetic particles have a structure composed of crystals, the amorphous rate X described later is less than 85%. When the filling rate is basically the same, the relative magnetic permeability is improved when the large particles have a nano-heterogeneous structure compared to when the large particles have a structure composed only of amorphous matter. In addition, it is preferred that the large particles have a structure composed of crystals, that is, a structure (nano-crystalline structure) with an average crystal particle size of 1 nm or more and 30 nm or less and a maximum crystal particle size of 100 nm or less. When the filling rate is basically the same, when the large particles have a nano-crystalline structure, the relative magnetic permeability of the magnetic core is further improved. In addition, in the soft magnetic particles that comprise crystallization, particularly nanocrystal, usually comprise multiple crystallizations in a particle. That is, the particle diameter of soft magnetic particles is different from crystal grain diameter. In addition, the calculation method of crystal grain diameter is not particularly limited. For example, the method of calculating crystal grain diameter and calculating crystal grain diameter by analyzing and evaluating crystallite size and by utilizing TEM to observe crystallization by XRD measuring the obtained half value width can be enumerated.
[0053] In the case where the soft magnetic particles have an amorphous structure, the soft magnetic particles may have a composition formula (Fe (1-(α+β)) X1 α X2 β ) (1-(a+b+c+d+e+f)) M a B b P c Si d C e S f The main components of
[0054] X1 may be one or more selected from Co and Ni,
[0055] X2 is one or more selected from Al, Mn, Ag, Zn, Sn, As, Sb, Cu, Cr, Bi, N, O and rare earth elements,
[0056] M is one or more selected from Nb, Hf, Zr, Ta, Mo, W, Ti and V,
[0057] 0≤a≤0.14
[0058] 0≤b≤0.20
[0059] 0≤c≤0.20
[0060] 0≤d≤0.14
[0061] 0≤e≤0.20
[0062] 0≤f≤0.02
[0063] 0.70≤1-(a+b+c+d+e+f)≤0.93
[0064] α≥0
[0065] β ≥ 0
[0066] 0≤α+β≤0.50.
[0067] The above composition formula is expressed in terms of atomic ratio.
[0068] In addition, the nanocrystal that soft magnetic particles (particularly large particles) comprise can be Fe-based nanocrystal.Fe-based nanocrystal is that average crystal grain size is nanoscale (specifically 0.1nm above and 100nm below), the crystal structure of Fe is bcc (body-centered cubic lattice structure) crystal.The method for calculating the average crystal grain size of Fe-based nanocrystal is not particularly limited.For example, the method for calculating the crystal grain size by analyzing the half-value width obtained by XRD measurement and the method for calculating the crystal grain size by utilizing TEM observation can be enumerated.In addition, confirming that the method for bcc crystal structure is not particularly limited either.For example, the method for confirming by utilizing XRD and the method for confirming by analyzing the electron beam diffraction pattern obtained by utilizing TEM can be enumerated.
[0069] In the present embodiment, the average crystal grain size of the Fe-based nanocrystals can be 1 to 30 nm. The saturation flux density of the soft magnetic particles having a structure composed of such Fe-based nanocrystals is easily increased, and the coercive force is easily reduced. That is, the soft magnetic properties are easily increased. That is, by including the soft magnetic particles, it is easy to make the magnetic core obtain low coercive force and high relative permeability. In addition, since the saturation flux density of the magnetic core containing the soft magnetic particles increases, the DC superposition characteristics of the magnetic core are improved. Therefore, by using soft magnetic particles having a structure composed of Fe-based nanocrystals, it is easy to improve the characteristics of the magnetic core.
[0070] In the case where the soft magnetic particles have a structure composed of Fe-based nanocrystals, the soft magnetic particles may have, for example, a composition formula (Fe (1-(α+β)) X1 α X2 β ) (1-(a+b+c+d+e+f)) M a B b P c Si d C e S f The main components of
[0071] X1 may be one or more selected from Co and Ni,
[0072] X2 is one or more selected from Al, Mn, Ag, Zn, Sn, As, Sb, Cu, Cr, Bi, N, O and rare earth elements,
[0073] M is one or more selected from Nb, Hf, Zr, Ta, Mo, W, Ti and V,
[0074] 0≤a≤0.14
[0075] 0≤b≤0.20
[0076] 0≤c≤0.20
[0077] 0≤d≤0.14
[0078] 0≤e≤0.20
[0079] 0≤f≤0.02
[0080] 0.70≤1-(a+b+c+d+e+f)≤0.93
[0081] α≥0
[0082] β ≥ 0
[0083] 0≤α+β≤0.50.
[0084] The above composition formula is expressed in terms of atomic ratio.
[0085] In the manufacturing method of the magnetic core described later, when the soft magnetic metal powder containing the soft magnetic particles having the above composition is subjected to heat treatment, Fe-based nanocrystals are easily precipitated in the soft magnetic particles. In other words, the soft magnetic particles having the above composition are easily used as the starting material of the soft magnetic metal powder having the soft magnetic particles having precipitated Fe-based nanocrystals.
[0086] Under the situation of separating out Fe-based nano-crystallization in soft magnetic particles by heat treatment, the soft magnetic particles before the heat treatment can have the structure consisting of only amorphous, and can also have the nano heterogeneous structure with initial microcrystal in amorphous. In addition, the average crystal grain size of initial microcrystal can be below 10nm above 0.3nm. In addition, under the situation of soft magnetic particles having the structure consisting of only amorphous or nano heterogeneous structure, the amorphization rate X described later is more than 85%.
[0087] In addition, for small particles, it is preferable that Fe is contained as a main component. In addition, it is preferable that Fe and at least one selected from Si and Ni are contained as a main component.
[0088] Here, containing Fe as a main component means that the content of Fe in the entire soft magnetic particles is 50 at % or more and 100 at % or less.
[0089] Containing Fe and at least one selected from Si and Ni as the main component means that the soft magnetic particles contain at least Fe and at least one selected from Si and Ni, and the total content of Fe, Si and Ni in the soft magnetic particles as a whole is 50at% to 100at%. In addition, the content of Fe can be 15at% to 95at%. The total content of Si and Ni can be 3at% to 90at%. In addition, the types of elements other than the main component are not particularly limited. For example, Co, Cr, Al, etc. can be cited.
[0090] By having the above-mentioned composition of the small particles, a magnetic core with high magnetic properties can be produced. That is, when the magnetic core has small particles containing Fe as the main component, the saturation flux density of the small particles can be increased. Therefore, the saturation flux density of the entire magnetic core can be increased, and the DC superposition characteristics of the magnetic core can be improved. In addition, when the magnetic core has small particles containing Fe and at least one selected from Si and Ni as the main components, the relative magnetic permeability of the small particles can be increased. Therefore, the relative magnetic permeability of the entire magnetic core can be improved.
[0091] The method for manufacturing the magnetic core according to the present embodiment will be described below, but the method for manufacturing the magnetic core is not limited to the method below.
[0092] First, a soft magnetic metal powder including the soft magnetic particles of the present embodiment is prepared. The soft magnetic metal powder of the present embodiment can be obtained by mixing a soft magnetic metal powder that will mostly become large particles and a soft magnetic metal powder that will mostly become small particles.
[0093] The soft magnetic metal powder that is ultimately mostly large particles can be produced by, for example, a gas atomization method.
[0094] In the gas atomization method, the molten metal obtained by melting the raw material metal is powderized by the gas atomization method to produce soft magnetic metal powder. The composition of the molten metal is set to the same composition as the composition of the large particles to be finally obtained. At this time, the molten metal drips from a container with a discharge port to a cooling part. The temperature of the molten metal is the injection temperature. There is no particular restriction on the injection temperature. For example, it is above 1200°C and below 1600°C. The higher the injection temperature, the easier it is for the average aspect ratio to approach 1, and the easier it is for the average particle size to decrease.
[0095] In addition, a gas nozzle having a gas injection port is arranged in a manner surrounding the above-mentioned discharge port. High-pressure gas (the injection pressure (gas pressure) is a gas of not less than 2.0 MPa and not more than 10 MPa) is injected from the gas injection port toward the molten metal dripping from the discharge port. As a result, the molten metal becomes a large number of droplets. By controlling the pressure of the high-pressure gas at this time, the particle size of the soft magnetic metal powder and the shape of the soft magnetic metal powder can be changed. Specifically, when the injection amount of the molten metal is the same, the higher the pressure of the high-pressure gas, the smaller the particle size of the soft magnetic metal powder obtained. That is, the particle size of the soft magnetic metal powder and the shape of the soft magnetic metal powder can be changed by the ratio of the pressure of the high-pressure gas to the injection amount of the molten metal.
[0096] As the gas injected from the gas injection port, an inert gas such as nitrogen, argon, helium, or a reducing gas such as ammonia decomposition gas is preferred. Alternatively, air may be used when the molten metal is difficult to oxidize.
[0097] The shape of the cooling part where the molten metal drips is not particularly limited, for example, it can be a cylinder with a cooling liquid flow that collides with the molten metal formed inside. In this case, in addition to the above-mentioned high-pressure gas pressure, by controlling the injection amount of the molten metal and the water pressure of the cooling liquid flow, the particle size of the large particles of the final magnetic core and the average aspect ratio of the large particles can also be changed. That is, the particle size and average aspect ratio of the large particles are controlled by controlling the balance of the injection amount of the molten metal, the high-pressure gas pressure and the water pressure of the cooling liquid flow. The injection amount of the molten metal can be more than 0.5kg / min and less than 4.0kg / min, and the water pressure can be more than 5.0MPa and less than 20.0MPa. Specifically, the larger the injection amount, the easier it is for the particle size of the large particles to increase. In addition, the smaller the water pressure, the easier it is for the average aspect ratio of the large particles to approach 1. That is, when changing the aspect ratio of the particles without changing the particle size, it is necessary to appropriately adjust the injection amount, the high-pressure gas and the water pressure of the cooling liquid flow.
[0098] The molten metal discharged into the coolant flow collides with the coolant flow and is further divided and miniaturized. The molten metal is miniaturized, and the shape of the miniaturized molten metal changes while being cooled and solidified to become a solid soft magnetic metal powder. The soft magnetic metal powder discharged together with the coolant is separated from the coolant in an external storage tank and taken out. In addition, the type of coolant is not particularly limited. For example, cooling water can be used. In addition, when no coolant is used, the soft magnetic metal powder that eventually becomes mostly large particles tends to contain coarse crystals with a crystal particle size exceeding 100nm.
[0099] In addition, the shorter the time from the molten metal dropping to the collision with the coolant flow, the less likely the molten metal is to be oxidized. Moreover, the rapid cooling effect is promoted, and the molten metal is more likely to become amorphous.
[0100] The obtained soft magnetic metal powder can be subjected to heat treatment. The conditions of the heat treatment are not particularly limited. For example, the heat treatment can be carried out at 400 to 700°C for 0.1 to 10 hours. By performing the heat treatment, when the fine structure of the particles is a structure having only amorphous materials or a nano-heterogeneous structure in which initial microcrystals exist in amorphous materials, the fine structure of the particles tends to become a structure containing nano-crystals. Moreover, there is a tendency for the coercivity of the soft magnetic metal powder to decrease. In addition, when the temperature of the heat treatment is too high, there is a tendency for the coercivity of the soft magnetic metal powder to increase.
[0101] The method for confirming the fine structure of the soft magnetic metal powder is not particularly limited. For example, it can be confirmed by XRD. In addition, the fine structure of the soft magnetic metal powder before powder pressing is usually the same as the fine structure of the particles contained in the magnetic core after powder pressing.
[0102] In this embodiment, the soft magnetic metal powder having an amorphization rate X of 85% or more shown in the following formula (1) has a structure or nano-heterostructure composed only of amorphous substances, and the soft magnetic metal powder having an amorphization rate X of less than 85% has a structure composed of crystals.
[0103] X=100-(Ic / (Ic+Ia)×100)…(1)
[0104] Ic: Crystalline scattering integrated intensity
[0105] Ia: Amorphous scattering integrated intensity
[0106] Regarding the amorphization rate X, X-ray crystal structure analysis is performed on the soft magnetic metal powder using XRD to identify the phase, and the peak of Fe or the compound after crystallization (Ic: crystalline scattering integrated intensity, Ia: amorphous scattering integrated intensity) is read, and the crystallization rate is estimated based on the peak intensity, and calculated using the above formula (1). The calculation method is further described in detail below.
[0107] The soft magnetic metal powder of this embodiment was subjected to X-ray crystal structure analysis using XRD, and the Figure 1 The curve shown in Figure 2 is used to fit the peak shape of the curve using the Lorentz function of the following formula (2), and we get Figure 2 The crystal component graph α showing the integrated intensity of crystalline scattering is shown in FIG. c , Amorphous component graph α showing the integrated intensity of amorphous scattering a , and the graph α that combines them c+a The amorphization rate X is obtained by the above formula (1) based on the crystalline scattering integrated intensity and the amorphous scattering integrated intensity of the obtained pattern. The measurement range is set to the range of diffraction angle 2θ = 30° to 60° in which the halo from the amorphous can be confirmed. Within this range, the error between the integrated intensity measured by XRD and the integrated intensity calculated using the Lorentz function is within 1%.
[0108]
[0109] h: peak height
[0110] u: peak position
[0111] w: half-value width
[0112] b: background height
[0113] The soft magnetic metal powder, which is mostly small particles in the end, is produced by various powdering methods such as a liquid phase method, a spray pyrolysis method, and a melting method.
[0114] In addition, by further processing the obtained soft magnetic metal powder using a ball mill, the aspect ratio can be changed. Specifically, by processing using a ball mill, the soft magnetic metal powder can be deformed, and the average aspect ratio of the small particles contained in the final magnetic core can be increased. The longer the processing time using the ball mill, the more the soft magnetic metal powder is deformed. In addition, the average aspect ratio of the small particles contained in the final magnetic core can be controlled by mixing the small particles that have been processed using the ball mill with the small particles that have not been processed using the ball mill.
[0115] The average particle size of the soft magnetic metal powder, which is mostly small particles, can be controlled by appropriately removing coarse powder and / or fine powder using an air classifier.
[0116] When a magnetic core is made of the soft magnetic metal powder of the present embodiment, first, the soft magnetic metal powder that will eventually become mostly large particles is mixed with the soft magnetic metal powder that will eventually become mostly small particles. The mixing method is not particularly limited. In addition, the mixing ratio can be, for example, such that the soft magnetic metal powder that will eventually become mostly large particles: the soft magnetic metal powder that will eventually become mostly small particles is 9:1 to 1:9 in terms of mass ratio.
[0117] Next, resin may be further added to the mixed soft magnetic metal powder as needed. The proportion of the resin to the entire magnetic core may be 1.5 mass % or more and 5.0 mass % or less. In addition, the powder after adding the resin and mixing may be granulated.
[0118] Then, the obtained powder is filled into a mold and compression-molded to obtain a magnetic core. The conditions for compression molding are not particularly limited. Compression molding can be performed at 1 t / cm 2 Above 8t / cm 2 The filling rate can be controlled by changing the molding pressure.
[0119] As mentioned above, the magnetic core of this embodiment was described, but the magnetic core of the present invention is not limited to the above-mentioned embodiment.
[0120] In addition, the use of the magnetic core of the present invention is not particularly limited. For example, coil components (magnetic components) such as inductors, choke coils, and transformers can be cited. Electronic devices using the magnetic core of the present invention, such as DC-DC converters, can also be cited.
[0121] Example
[0122] Hereinafter, the present invention will be further described based on detailed examples, but the present invention is not limited to these examples.
[0123] Experimental Example 1
[0124] In Sample No. 1 to 28, the soft magnetic metal powders were produced by gas atomization, most of which were eventually large particles. 0.800 Nb 0.070 B 0.098 P 0.030 S 0.002 .
[0125] At this time, the injection amount of the molten metal, the temperature of the molten metal (injection temperature), the injection gas pressure and the water pressure of the coolant flow were set to the values shown in Table 2, and soft magnetic metal powders with average aspect ratios A1 of large particles in the final magnetic core of 1.01, 1.30, 1.50, and 2.00 were produced. The gas type used was Ar. In addition, other conditions were also appropriately controlled so that the average particle size (D50) of the obtained soft magnetic metal powder based on the number of particles reached 10.3μm.
[0126] Then, the obtained soft magnetic metal powder was heat-treated at 600° C. for 1 hour in an Ar atmosphere.
[0127] It was confirmed that the average particle size (D50) of the obtained soft magnetic metal powder based on the number of particles was 10.3 μm. The average particle size based on the number of particles was measured using Morphologi G3. In addition, XRD and STEM confirmed that each soft magnetic metal powder was a nanocrystalline structure. In addition, after using the obtained soft magnetic metal powder to make a magnetic core according to the method described below, the cross section of the magnetic core was observed using SEM at a size that at least 10 or more soft magnetic particles could be observed. The SEM observation was repeated in such a way that a total of more than 100 soft magnetic particles were observed. Then, the Heywood diameter of more than 100 soft magnetic particles was measured. As a result, the average particle size (D50) of the Heywood diameter of the soft magnetic particles reached 7.5 μm. The average particle size of the soft magnetic particles measured by observing the cross section of the magnetic core is smaller than the actual average particle size of the soft magnetic metal powder because any part of the soft magnetic metal powder is cut off when the cross section of the magnetic core is cut off.
[0128] In samples No. 1 to 28, a soft magnetic metal powder that is mostly small particles is produced by spray pyrolysis. The composition is Fe 100at%. In addition, an air flow classifier is used to appropriately remove coarse powder and / or fine powder, thereby controlling the average particle size (D50) of the small particle powder to 1.5μm. In addition, at this moment, the soft magnetic metal powder is in a shape close to a true sphere, and the average aspect ratio of the soft magnetic particles when the soft magnetic metal powder is used to make a magnetic core is 1.00. In addition, after using the obtained soft magnetic metal powder to make a magnetic core according to the method described below, the cross section of the magnetic core is observed using SEM to a size that can observe at least 10 or more soft magnetic particles. Repeat the SEM observation in such a way that a total of more than 100 soft magnetic particles are observed. Then, the Heywood diameter of more than 100 soft magnetic particles is measured. As a result, the average particle size (D50) of the Heywood diameter of the soft magnetic particles reaches 1.1μm.
[0129] Next, the powder was treated in a ball mill to produce soft magnetic metal powders having average aspect ratios A2 of 1.00, 1.30, 1.50, 1.70, 2.00, 2.50, and 3.00 for the small particles in the final magnetic core. Table 3 shows the treatment times.
[0130] Then, the soft magnetic metal powder, which eventually became mostly large particles, was coated with zinc phosphate to have an average thickness of 20 nm. Also, the soft magnetic metal powder, which eventually became mostly small particles, was coated with zinc phosphate to have an average thickness of 10 nm.
[0131] Then, the soft magnetic metal powder that will eventually become mostly large particles is mixed with the soft magnetic metal powder that will eventually become mostly small particles at a mass ratio of 8:2. When the density of the powders is the same, the above mass ratio is basically consistent with the area ratio (S1:S2). In addition, the mass ratio of large particles to small particles can also be calculated based on the area ratio of large particles to small particles and the density of each particle, and 100 parts by mass of the mixed soft magnetic metal powder is further diluted and added with acetone in such a way that the epoxy resin reaches 3 parts by mass. Then, the agglomerate obtained by kneading and drying with a kneader is granulated so that the average particle size is less than 355μm in volume particle size distribution to obtain particles. It is filled into a mold. The shape of the mold makes the shape of the final magnetic core annular.
[0132] Next, the soft magnetic metal powder is pressed and molded. The molding pressure is controlled so that the filling rate of the magnetic core obtained at this time reaches the value shown in Table 1. Specifically, the molding pressure is controlled to be 1 to 8 ton / cm 2 within the range.
[0133] For each experimental example, a cross section cut parallel to the molding direction (height direction) was observed. Specifically, the observation range was set by SEM so that more than 10 large particles could be observed. The magnification was set to 1000 times. In addition, for each experimental example, it was confirmed that the area ratio of large particles was more than 10% and the area ratio of small particles was more than 10% relative to all the soft magnetic particles contained in the magnetic core.
[0134] Then, the average aspect ratio A1 of the large particles in the magnetic core of each experimental example, the average elliptical circularity of the large particles, the average aspect ratio A2 of the small particles, the maximum value of the Heywood diameter of the soft magnetic particles, the filling rate, the relative magnetic permeability and the withstand voltage characteristics were measured. A1, A2, the average elliptical circularity of the large particles, the maximum value of the Heywood diameter and the filling rate of each magnetic core were calculated based on the SEM image. The relative magnetic permeability was measured using IMPEDANCE / GAIN-PHASEANALYZER (manufactured by Yokogawa Hewlett-Packard Company, 4194A). The relative magnetic permeability was evaluated as good when it was higher than 40.
[0135] Regarding the withstand voltage characteristics of each magnetic core, a pair of In-Ga electrodes were formed on the magnetic core, and a pair of copper plates were used to clamp the pair of In-Ga electrodes. A voltage was applied to the pair of copper plates, and the voltage when 1 mA current was flowing was evaluated. In this experimental example, the case of 50 V / mm or more was evaluated as good. The results are shown in Table 1.
[0136]
Table 1
[0137]
[0138]
Table 2
[0139]
[0140]
Table 3
[0141]
[0142] According to Table 1, all the embodiments that satisfy 1.00≤A1≤1.50, 1.30≤A2≤2.50, and A1<A2 have significantly improved withstand voltage characteristics compared to the comparative examples that do not satisfy any of 1.00≤A1≤1.50, 1.30≤A2≤2.50, and A1<A2. In addition, the filling rate is equal in each embodiment and each comparative example, and the relative permeability is good in each embodiment.
[0143] Experimental Example 2
[0144] In Experimental Example 2, the same conditions as those of Experimental Example 1 were used except for the aspects described below. In Experimental Example 2, the gas pressure was changed when making the soft magnetic metal powder that eventually became mostly large particles. And the average particle size of the soft magnetic metal powder and the average aspect ratio A1 of the large particles in the finally obtained magnetic core reached the values shown in Table 5, respectively. In addition, the air flow classifier was used to appropriately remove the coarse powder and / or fine powder, so as to control the average particle size of the soft magnetic metal powder that eventually became mostly small particles to reach the value shown in Table 4. In addition, for each embodiment, it was confirmed in the same way as in Experimental Example 1 that the area ratio of large particles was 10% or more, the area ratio of small particles was 10% or more, the average ellipticity of large particles was 0.95 or more, and the soft magnetic metal powder that eventually became mostly large particles had a nanocrystalline structure.
[0145]
Table 4
[0146]
[0147]
Table 5
[0148]
[0149] According to Table 4, even if the average particle size of the soft magnetic metal powder is changed, in all embodiments satisfying 1.00≤A1≤1.50, 1.30≤A2≤2.50, and A1<A2, the withstand voltage characteristics are good despite the high relative magnetic permeability. In addition, compared with sample No. 31 in which the maximum value of the Heywood diameter of the soft magnetic particles exceeds 40μm, the withstand voltage characteristics of the other embodiments are better.
[0150] Experimental Example 3
[0151] In Experimental Example 3, the atomization conditions were changed from those in Experimental Example 1, and the average aspect ratio A1 and average ellipticity of large particles were controlled. The atomization conditions are shown in Table 7. The atomization conditions of Samples No. 38 to 42 were the same as those of Sample No. 9.
[0152] In Experimental Example 3, for the soft magnetic metal powders that eventually become mostly large particles, the case where each soft magnetic metal powder has a nanocrystalline structure after heat treatment in the same manner as in Experimental Examples 1 and 2, and the case where each soft magnetic metal powder has a structure composed only of amorphous or a nano heterogeneous structure without heat treatment were prepared. Among them, in the case where no heat treatment was performed, the average particle size (D50) of the soft magnetic metal powders that eventually become mostly large particles evaluated by Morphologi G3 reached 10.4μm on a number basis.
[0153] In addition, in Sample Nos. 39 and 41, most of the soft magnetic metal powders eventually became small particles, except for the composition mainly composed of Fe and Ni, that is, Ni 80 Fe 20 Except for this point, the soft magnetic metal powder was prepared in the same manner as in Experimental Examples 1 and 2. In addition, in Samples No. 40 and 42, most of the soft magnetic metal powders that eventually became small particles were the same as those in Experimental Examples 1 and 2. 57.1 Si 28.6 Cr 14.3 Except for this point, the same procedure as in Experimental Examples 1 and 2 was carried out to prepare soft magnetic metal powder.
[0154] The above-mentioned soft magnetic metal powders were appropriately combined to produce magnetic cores. The results are shown in Table 6.
[0155]
[0156]
Table 7
[0157]
[0158] According to Tables 6 and 7, the lower the average elliptical roundness of the large particles, the lower the withstand voltage. In addition, even if the composition of the small particles is changed, the withstand voltage characteristics do not change significantly, but when the microstructure of the large particles is a structure composed only of amorphous or a nano-heterogeneous structure, the relative permeability is lower than that of the nano-crystalline structure.
[0159] Experimental Example 4
[0160] In Experimental Example 4, the same conditions were used for Sample No. 9 except that the amount of zinc phosphate added was changed and the coating thickness of each particle was changed.
[0161]
Table 8
[0162]
[0163] According to Table 8, there is a similar tendency even when the coating thickness is changed. In addition, as the coating thickness increases, the withstand voltage characteristics improve, but there is a tendency for the relative magnetic permeability to decrease.
[0164] Experimental Example 5
[0165] In Experimental Example 5, for the soft magnetic metal powder that will eventually become mostly large particles, the crystal structure is changed by controlling the composition and atomization conditions. The composition and crystal structure are shown in Table 9. Specifically, the atomization conditions of Samples No. 51 to 56 are the same as those of Sample No. 1 shown in Table 2. The atomization conditions of Samples No. 57 to 62 are the same as those of Sample No. 1, except that cooling water is not sprayed. No heat treatment is performed in Samples No. 51 to 62. Other aspects are the same as Experimental Example 1. In addition, the composition of the large particles is recorded as an atomic ratio.
[0166] Table 9 shows the results.
[0167]
[0168] According to Table 9, all the embodiments satisfying 1.00≤A1≤1.50, 1.30≤A2≤2.50, and A1<A2 have significantly improved withstand voltage characteristics compared to the comparative examples that do not satisfy any of 1.00≤A1≤1.50, 1.30≤A2≤2.50, and A1<A2. In addition, the filling rate is equal in each embodiment and each comparative example, and the relative magnetic permeability is good in each embodiment. In addition, in the embodiments in which the fine structure of large particles is a structure composed only of amorphous materials (samples No. 52 to 55) and the embodiments in which the fine structure of large particles is a structure composed of crystals and contains coarse crystals with a grain size exceeding 100nm (samples No. 58 to 61), the relative magnetic permeability is reduced compared to the embodiments in which the fine structure of large particles is a structure composed of nanocrystals (samples No. 5, 13, 17, 21).
[0169] Experimental Example 6
[0170] In Experimental Example 6, for Samples No. 1 and 5, the mixing ratio of the soft magnetic metal powder that will eventually become mostly large particles and the soft magnetic metal powder that will eventually become mostly small particles was changed to achieve S1:S2 as shown in Table 10. In addition, unlike Experimental Examples 1 to 5, the molding pressure was unified to 4 t / cm 2 This is to evaluate the change in filling rate when S1:S2 is changed. Other aspects are implemented under the same conditions. Table 10 shows the results.
[0171]
Table 10
[0172]
[0173] The examples and comparative examples having the same S1:S2 are compared according to Table 10. The examples satisfying all of 1.00≤A1≤1.50, 1.30≤A2≤2.50, and A1<A2 have improved withstand voltage characteristics compared to the comparative examples not satisfying any of 1.00≤A1≤1.50, 1.30≤A2≤2.50, and A1<A2.
[0174] According to Table 10, if the molding pressure is the same, the filling rate increases when S1:S2 is 8:2. When S1:S2 is 8:2, the relative magnetic permeability is the highest. There is a tendency that the withstand voltage characteristics improve as the ratio of S2 to S1 increases. However, the filling rate decreases as the ratio of S2 to S1 increases, and there is a tendency that the relative magnetic permeability decreases.
[0175] For each embodiment of Table 10, the molding pressure is set at 1 to 8 t / cm 2 The filling rate changes between the ratios of S1 and S2, and the change in the filling rate is confirmed. When comparing the embodiments obtained by the same molding and pressing, at any molding pressure, the filling rate and relative magnetic permeability both increase when S1:S2 is 8:2. There is a tendency that the greater the ratio of S2 to S1, the higher the withstand voltage characteristics. However, the greater the ratio of S2 to S1, the lower the filling rate, and there is a tendency for the relative magnetic permeability to decrease. Therefore, it can be confirmed that the filling property is best when S1:S2 is 8:2.
Claims
1. A magnetic core, characterized in that: The magnetic core includes large particles, which are soft magnetic particles having a Heywood diameter of 5 μm or more and 25 μm or less, and small particles, which are soft magnetic particles having a Heywood diameter of 0.5 μm or more and 3 μm or less, on a cross section thereof. The average aspect ratio of the large particles is set to A1, and the average aspect ratio of the small particles is set to A2, satisfying 1.00≤A1≤1.50, 1.30≤A2≤2.50, and A1<A2.
2. The magnetic core according to claim 1, characterized in that In the cross section of the magnetic core, the Heywood diameter of the soft magnetic particles that are neither the large particles nor the small particles is 40 μm or less.
3. The magnetic core according to claim 1, characterized in that: The average ellipticity of the large particles in the cross section of the magnetic core is 0.93 or more.
4. The magnetic core according to claim 2, characterized in that: The average ellipticity of the large particles in the cross section of the magnetic core is 0.93 or more.
5. The magnetic core according to any one of claims 1 to 4, characterized in that: The large particles include nanocrystals.
6. The magnetic core according to any one of claims 1 to 4, characterized in that: The Fe content in the entire small particles is 50 at % or more and 100 at % or less.
7. The magnetic core according to claim 5, characterized in that: The Fe content in the entire small particles is 50 at % or more and 100 at % or less.
8. The magnetic core according to any one of claims 1 to 4, characterized in that: The small particles contain at least Fe and at least one selected from Si and Ni, and a total content of Fe, Si, and Ni in the entire small particles is 50 at % or more and 100 at % or less.
9. The magnetic core according to claim 5, characterized in that: The small particles contain at least Fe and at least one selected from Si and Ni, and a total content of Fe, Si, and Ni in the entire small particles is 50 at % or more and 100 at % or less.
10. A magnetic component, characterized in that: A magnetic core comprising the magnetic core according to any one of claims 1 to 9.
11. An electronic device, characterized in that: A magnetic core comprising the magnetic core according to any one of claims 1 to 9.
Citation Information
Patent Citations
JP1976010660B1
Coil encapsulating magnetic component and method of manufacturing the same
JP2003309024A
Composite magnetic material, core using the same, and magnetic element
JP2004197218A
Complex magnetic material and method for manufacturing inductor using the same
JP2004363466A
Compound for rare earth system nanocomposite magnet, and its manufacturing method
JP2006287044A